Pedagogical strategies for supporting learning and student well-being in environmentally sustainable healthcare - Jones, Nara; Horton, Graeme; Guppy, Michelle; Brown, Georgia; Boulton, John (Frontiers in Medicine, 2025)
Planetary health education needs fresh approaches to engage learners and educators in positive visions and future planning to navigate the societal challenges of climate change. The human health impacts of the climate crisis, environmental degradation and pollution are far-reaching and compounding in nature. International leaders in healthcare are recognizing the time-pressured opportunity to mobilize and motivate colleagues to optimize health outcomes by addressing these issues. Healthcare systems across the globe contribute significantly to ecological footprints through greenhouse gas emissions and consumption of various polluting materials. Therefore, the necessity to prepare future health professionals to identify and manage environmental health conditions in their patients, as well as foster their future role as leaders and advocates in sustainable healthcare is acute. Health education organizations have begun to appreciate this need and have developed learning objectives to guide curricula. In the development and implementation of content on environmentally sustainable healthcare, an important consideration is the affective and moral distress from the confronting and often overwhelming nature of the topic. The main objective in teaching planetary health is to equip learners with the tools and skills to address the relevant health issues in their professional role whilst providing the support necessary for them to accept these harsh realities. The University of Newcastle and University of New England Joint Medical Program's, four-week course in Sustainable Healthcare aims to meet this objective. In this article we discuss how our curriculum utilizes Self-Determination Theory (SDT) and other psychological strategies to support learners' well-being and motivation. SDT explains the need for supporting autonomy, relatedness and competence in the learning environment. Strategies employed to address these include providing students with the opportunity to select discussion topics that they contribute to, maximizing choice of focus for the assessment task, utilizing personal reflections, case-based learning scenarios and incorporating presentations from relatable industry leaders.